2007
DOI: 10.1159/000110684
|View full text |Cite
|
Sign up to set email alerts
|

Open-Access Upper Gastrointestinal Endoscopy a Decade after the Introduction of Proton Pump Inhibitors and Helicobacter pylori Eradication: A Shift in Endoscopic Findings

Abstract: Background/Aim: Over the past 15 years, there were considerable changes in factors associated with the development and treatment of upper gastrointestinal symptoms, of which the introduction of proton pump inhibitors and Helicobacter pylori eradication in guidelines for treatment of patients with dyspepsia are the most prominent: findings at open-access upper gastrointestinal endoscopy have not been evaluated properly ever since. This study aims to compare the current prevalence of upper gastrointestinal endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…5,8 A single-centre Dutch study observed an increase in the prevalence of BO from 2.6 to 4.7% between the 1990s and 2004. 7 A study in Northern Ireland showed a 159% increase from 23.9 to 62 cases per 100 000 PYs between the periods of 1993-1997 and 2002-2005. 5 The rise in incidence may partially be explained by a 'true' increase of BO and partially by better clinical awareness of physicians resulting in more gastroscopies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,8 A single-centre Dutch study observed an increase in the prevalence of BO from 2.6 to 4.7% between the 1990s and 2004. 7 A study in Northern Ireland showed a 159% increase from 23.9 to 62 cases per 100 000 PYs between the periods of 1993-1997 and 2002-2005. 5 The rise in incidence may partially be explained by a 'true' increase of BO and partially by better clinical awareness of physicians resulting in more gastroscopies.…”
Section: Discussionmentioning
confidence: 98%
“…3 Endoscopic surveillance for OAC among patients with BO is therefore recommended. 4 Several studies reported increasing incidence rates (IRs) of BO, [5][6][7][8] although these vary widely, from 23 to 62 cases per 100 000 person-years (PYs). 5,8 A single-centre Dutch study observed an increase in the prevalence of BO from 2.6 to 4.7% between the 1990s and 2004.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one outstanding dilemma is the frequent overlap between dyspeptic and reflux symptoms [11]. The decline of both H. pylori and peptic ulcer prevalence and the parallel increase in gastro-oesophageal reflux disease may also have an impact on the association between dyspeptic symptoms and endoscopic findings [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to avoid a type-2 error we would have had to collect an almost unrepeatable number of malignancy diagnoses. It is, however, worth stressing that the painsymptom caused by a probable duodenal ulcer is what forces patients to ask for a reduction inwaiting time [18]. In our opinion, this is an important management finding, insofar as an antacidtherapy could be prescribed to patients who cannot be fast-tracked.…”
Section: Discussionmentioning
confidence: 99%